A case of neurocysticercosis in immigrant worker presented with seizures - Khamshah, Amir Safuan; Mustapa, Nur Izati; Awang Hamat, Rukman (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Neurocysticercosis is an infection of the central nervous system (CNS) by larval stage of Taenia solium (pork tapeworms) called cysticerci. Humans may acquire the infection through ingestion of T. solium embryonated eggs after consuming contaminated undercooked food or water. Being a multiracial country where pig farming is limited and consumption of raw or undercooked food is an uncommon practice, the prevalence of neurocysticercosis in Malaysia is presumably low. However, through immigration and international travel, cases of neurocysticercosis may go underreported. Due to unfamiliarity with the disease, cases of neurocysticercosis also may be missed in Malaysia. Therefore, thorough history taking and physical examinations with high index of suspicion are required by the clinicians to warrant proper investigations in order to meet the diagnosis of neurocysticercosis. Patients diagnosed with neurocysticercosis should be treated cautiously with anthelmintic, to avoid unwanted overwhelming immunological response that can lead to unfavourable outcomes. This is a case report of a foreign worker who presented with first onset of focal seizure associated with intermittent headache.